(untitled) (Crossing the Border: International Journal of Interdisciplinary Studies, 2014)
Demands are increasing on businesses to do their part to respond to the threat of climate change based on their influential position within the global community. If companies can effectively integrate strategy, people, processes and technology in the pursuit of initiatives that respond to climate change, the result can be a powerful tool of long-term value creation. But what exactly are the impacts of climate change on businesses is the focus of the study? Varying levels of appreciation of the effects of climate change on business operations are rooted in the difference between direct and indirect impacts of climate change. So, the question is how business gets impacted by direct and indirect differences? Some of these effects are potentially threatening to sustainable high performance changing climatic conditions. What are some specific steps businesses can take to respond to both the threats and opportunities presented by climate change? To support a fact-based discussion of the business impact of climate change, primary qualitative survey conducted to Nepalese business houses and as secondary of a global context. Business initiatives in response to climate change are generally spread across a broad range of activities, risking fragmentation. Climate change may transform parts of our planet, the context and presumptions by which businesses typically operate today. This transformation is a result of both the direct impacts of climate change on business operations, as well as its indirect effects. Many business leaders feel a profound responsibility to do their part to respond to the pressing global challenge represented by climate change. But apart from this sense of societal obligation, business leaders must also be attuned to how climate change is altering the dynamics of markets, competition and profitability. DOI: http://dx.doi.org/10.3126/ctbijis.v2i1.10816 Crossing the Border: International Journal of Interdisciplinary Studies Vol.2(1) 2014: 93-112